Intersticiální cystitida--diagnostika a lécba - Zámecník, L; Hanu, T; Pavlík, I; Dundr, P; Povýsil, C (Casopis lekaru ceskych, 2005)
Interstitial cystitis is a chronic, non-bacterial inflammatory disorder of the wall of the urinary bladder and it manifests with very painful symptoms. Initially it can resemble a bacterial inflammation of the urinary bladder. This syndrome is characterised with motor and sensory dysfunction of the urinary bladder. The difficulties can be classified into so-called syndrome of the chronic pelvic pain. Increasing incidence, chronicity of this disorder and specific treatment leads to the reinterpretation of the chronic inflammation of the urinary tract diagnosed in the past and to the modification of the treatment of these patients. Because of the polymorphic difficulties and the psychosomatic manifestations, IC can lead to invalidity of the patient.
Keywords: senioři; pánevní bolest; senioři nad 80 let; Prognosis; Chronic Disease; mladiství; chronická nemoc; Middle Aged; Urinary Bladder; Adult; močový měchýř; Aged, 80 and over; ženské pohlaví; prognóza; Humans; Cystitis, Interstitial; Pelvic Pain; lidé středního věku; dospělí; intersticiální cystitida; Female; Aged; Adolescent; lidé